2014
DOI: 10.1063/1.4902253
|View full text |Cite
|
Sign up to set email alerts
|

Certifying the quantumness of a generalized coherent control scenario

Abstract: We consider the role of quantum mechanics in a specific coherent control scenario, designing a "coherent control interferometer" as the essential tool that links coherent control to quantum fundamentals. Building upon this allows us to rigorously display the genuinely quantum nature of a generalized weak-field coherent control scenario (utilizing 1 vs. 2 photon excitation) via a Bell-CHSH test. Specifically, we propose an implementation of "quantum delayed-choice" in a bichromatic alkali atom photoionization e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…will no doubt address 'nonideal' effects, such as multimode irradiation, which may not necessarily be deleterious. For example, it has been shown that interference of the ionization paths in the presence of a photoionizing laser field and its second harmonic leads to the possibility of coherent control of the spin of the photoelectron [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…will no doubt address 'nonideal' effects, such as multimode irradiation, which may not necessarily be deleterious. For example, it has been shown that interference of the ionization paths in the presence of a photoionizing laser field and its second harmonic leads to the possibility of coherent control of the spin of the photoelectron [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…5 can be implemented with a combination of Eqs. ( 134), (136) and (141). The existence of a single direction of detection K+ [Eq.…”
Section: The Proposed Experimentsmentioning
confidence: 99%
“…Here, we apply this formalism to a specific example used throughout the remainder of the article, phase-coherent control of the spin polarization of an electron emitted in an 1 vs. 2 photoionization process from a heavy alkali atom [136]. This control scenario is an extension of Elliott's twocolor photoionization experiments on alkali atoms [14,15,32,33], which demonstrated that the angular distribution of an emitted photoelectron can be controlled by the relative phase between two ionizing laser beams.…”
Section: Application To Photoelectron Spin Polarization Control In Almentioning
confidence: 99%